Complement deficiencies in humans - Tedesco, Francesco (Henry Stewart Talks, 2018)
Organization and functions of the complement system, Frequency of inherited deficiencies in the general population, Deficiencies of components and regulators of the complement system and their disease association, Diagnostic approaches and therapeutic strategies to identify and to control the complement defects